Are neurodevelopmental structural pathologies of the insula potential biomarkers for schizophrenia risk? - Susanna Gebhardt; Henry A. Nasrallah (Biomarkers in Neuropsychiatry, 2024)
The insula is a significant neural region associated with the development and clinical symptoms of schizophrenia. Here, we provide an overview of the role of the insula in a non-pathological context, as well as its function in schizophrenia, discussing how structural and functional changes to the insula can provide insight into the etiology of schizophrenia and contribute to potential therapeutic intervention.